Nutritional status assessment of 6-59 months age children in rural Yadgir, Karnataka state, India - Chittapur, Dhanaraj; Patil, Shilpa S.; Lakshmanappa, Shruthi (International Journal Of Community Medicine And Public Health, 2024)
Background: Childhood undernutrition contributes to childhood diseases and is a major cause of child mortality in India. According to National Family Health Survey (NFHS-5), 32% under-five children in India were under-weight, and 36% were stunted. In Karnataka, the prevalence of underweight among under-five children was 33% and stunting 35%. The objective of the study was to assess the nutritional status of under five-years children in rural communities. Methods: A community based cross sectional study was conducted among 1887 under-five children from rural Yadgir, Karnataka. Weight and height of children were measured using standard protocols. The World Health Organization (WHO) Anthro software version 3.2.2.1 was used for analyzing data. Children whose Z-scores on weight-for-age, height-for-age and weight-for-height indices were below -2SD from the median of the WHO reference population were considered as underweight, stunted, and wasted respectively. Results: The result revealed that 53.6% of children were stunted, 39.4% were underweight and 15.3% were wasted. Severe forms of underweight, stunting and wasting were observed among 9.4%, 24.2% and 4% children respectively. The frequency of being underweight and stunted has increased with age, which was accelerated after 6 months and about 34% and 52% of children were underweight and stunted by the age 12-23 months. While wasting was higher among children aged 6-11 (24.2%) months than their counterparts. Conclusions: Special attention is required to reduce nutrition vulnerability among young children (12-24 months). An appropriate strategy needs to be implemented to educate rural mothers on the importance of exclusive breastfeeding and complementary feeding practices.